Advantages and economics of heat pump based air handling units for ventilation and air conditioning in commercial and industrial sectors - Bezrondy, M.; Misiura, T. (Energy and Automation, 2023)
The current article contains a comparative thermodynamic analysis of the two most popular solutions for general ventilation and air conditioning: supply-exhaust units based on built-in circuits of heat pumps or external compressor-condenser units as the main energy sources. The theoretical analysis was carried out under the same constant conditions in the cold mode of operation in the warm season, when it is necessary to cool the supply air. As a result of the research, graphs of the dependences of the parameters of the two systems (temperature and air humidity at the nodal points of the systems, energy efficiency of HP or CCU and schemes as a whole) were constructed on the parameters of the outside air and the needs for ventilation and air conditioning inside the premises according to the project conditions. The purpose of this article is to theoretically investigate which of the schemes has a higher efficiency under the given conditions. The researched theoretical models of the two systems can be used to assess the feasibility of one or another scheme depending on the project, as well as during the design of the AHU. Using this analysis, it is possible to accurately and effectively select such real plant components as heat exchangers, compressors, heat exchangers, etc. for the production of supply and exhaust units.Key words: ventilation, air conditioning, supply and exhaust units, cooling coefficient, recuperation, air recirculation, KKB, heat pump